2014
DOI: 10.5483/bmbrep.2014.47.12.290
|View full text |Cite
|
Sign up to set email alerts
|

PV.1 induced by FGF-Xbra functions as a repressor of neurogenesis in Xenopus embryos

Abstract: During Xenopus early development, FGF signaling is involved in mesoderm formation and neurogenesis by modulating various signaling cascades. FGF-MAPK signaling induces Xbra expression, which maintains mesodermal fate through an autocatalytic-loop. Interestingly, previous reports have demonstrated that basic FGF (bFGF) treatment alone does not induce neurogenesis in ectodermal explants, even though FGF signaling inhibits BMP signaling via phosphorylation in Smad1 linker region. In addition, the overexpression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…Moreover, the C-terminal domain of PV.1 leads the inhibition of dorsal fate determination and neural inhibition (Hawley et al, 1995; Hwang et al, 2002; Hwang et al, 2003). Recent studies observed that FGF signaling plays a dual role to regulate the BMP-4/Smad-1 signaling (Pera et al, 2003; Yoon et al, 2014b). FGF signaling inhibits BMP-4/Smad-1 signaling through inhibiting the Smad-1 activity in an MAPK-dependent manner (Pera et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the C-terminal domain of PV.1 leads the inhibition of dorsal fate determination and neural inhibition (Hawley et al, 1995; Hwang et al, 2002; Hwang et al, 2003). Recent studies observed that FGF signaling plays a dual role to regulate the BMP-4/Smad-1 signaling (Pera et al, 2003; Yoon et al, 2014b). FGF signaling inhibits BMP-4/Smad-1 signaling through inhibiting the Smad-1 activity in an MAPK-dependent manner (Pera et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, FGF alone is not sufficient to induce neurogenesis in Xenopus embryos (Pera et al, 2003). Later on, a study showed that FGF signaling positively regulates expression of PV.1 (A transcriptional factor of BMP-4 signaling) in a Xbra-dependent manner, causing to neural inhibition (Yoon et al, 2014b). The involvement of BMP-4/Smad-1 and FGF-Xbra signaling may facilitate a signaling crosstalk in the regulation of PV.1 expression during embryonic development of Xenopus.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations